Epigenetic reprogramming of fallopian tube fimbriae in BRCA mutation carriers defines early ovarian cancer evolution - Thomas E. Bartlett (Nature Portfolio, 2016)
Women with germline variants in BRCA genes are predisposed to ovarian cancer. In this study, the authors demonstrate that fimbrial tissue from the ovary, the site of ovarian cancer, in BRCAmutant carriers contains marked DNA methylation changes compared with the proximal region of the ovary.